2015
DOI: 10.1371/journal.pone.0132927
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and the Subsequent Risk of End-Stage Renal Disease – Usefulness of 30% Decline in Estimated GFR over 2 Years

Abstract: BackgroundA goal of searching risk factors for chronic kidney disease (CKD) is to halt progressing to end-stage renal disease (ESRD) by potential intervention. To predict the future ESRD, 30% decline in estimated GFR over 2 years was examined in comparison with other time-dependent predictors.MethodsCKD patients who had measurement of serum creatinine at baseline and 2 years were enrolled (n = 701) and followed up to 6 years. Time-dependent parameters were calculated as time-averaged values over 2 years by a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 40 publications
5
53
0
Order By: Relevance
“…To date, epidemiological cohort studies on CKD patients in Japan have reported the correlation between percentage changes in eGFR and risk of ESRD [18,20]. According to the study on CKD patients by Chang et al, decrease in percentage changes in eGFR of more than 30% over 2 years correlated with ESRD strongly [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, epidemiological cohort studies on CKD patients in Japan have reported the correlation between percentage changes in eGFR and risk of ESRD [18,20]. According to the study on CKD patients by Chang et al, decrease in percentage changes in eGFR of more than 30% over 2 years correlated with ESRD strongly [18].…”
Section: Discussionmentioning
confidence: 99%
“…To date, epidemiological cohort studies on CKD patients in Japan have reported the correlation between percentage changes in eGFR and risk of ESRD [18,20]. According to the study on CKD patients by Chang et al, decrease in percentage changes in eGFR of more than 30% over 2 years correlated with ESRD strongly [18]. On the other hand, in a CKD Japan Cohort (Chronic Kidney Disease Japan Cohort, CKD-JAC) study, the relationship between patient distribution and risk of ESRD based on percentage changes in eGFR over 1-2 years indicated 30 or 40% to be the surrogate endpoints [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective CKD cohort already reported (n = 803) was used [9][10][11][12], and in the current study the propensity score analysis was used in such a way as used in the previously published articles [9,12]. Inclusion criteria consisted of CKD stage 3 to 4, age 20 to 84 years and follow-up period ≥ 1 year.…”
Section: Study Protocol and Ethical Statementmentioning
confidence: 99%
“…Death was treated as censoring because the present study focused on the effect of hematuria on the subsequent ESRD rather than the risk of mortality [11]. Competing risk method was not employed due to a small portion of death censoring (n = 10).…”
Section: Endpoints Of Renal Outcomesmentioning
confidence: 99%